A cross-sectional study on well-being of Malaysian police retirees - Md. Yassin, Sulaiman; Alby, Jeffrey Lawrence D'Silva (Penerbit Universiti Malaysia Terengganu, 2016)
Undeniably well-being is a growing area of research that can be measured using both objective and subjective indicators. Very few attempts were made in the Malaysian context to measure the level of well-being of the different segments of the community. Hence, this study was carried out to measure the well-being of Malaysian police retirees. This is a cross-sectional study using a survey instrument that was developed from previous studies. A total of 420 police retirees took part in this study from the five zones in Malaysia. The results showed that the objective well-being of police retirees in Malaysia was less satisfactory particularly on issues pertaining to finance and real income. On the other hand, Malaysian police retirees had a satisfactory level of the subjective well-being. However, much attention needs to be given to further enhance the subjective work and economic well-being of police retirees. In line with this, the study suggests that more efforts should be implemented to enhance the well-being of Malaysian police retirees concerning areas on finance, housing, and work and family well-being.